2015
DOI: 10.1002/2014gl062921
|View full text |Cite
|
Sign up to set email alerts
|

A “high 4He/3He” mantle material detected under the East Pacific Rise (15°4′N)

Abstract: We investigate in details helium isotope data reported in Mougel et al. (2014) for 14 basaltic samples collected on the East Pacific Rise by submersible (15°4′N) where the ridge interacts with the Mathematician seamounts. Samples locations are separated by only few hundred meters across a 15 km along-axis profile. The data reveal a strong geochemical variability that has never been observed at such high spatial resolution for helium isotope compositions. Moreover, they reveal an unusually high 4 He/ 3 He mantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…It is the broadest and shallowest segment of the entire northern EPR with an unusually prominent along-axial-ridge, up to 15 km wide at its base and up 750 m high with respect to the adjacent abyssal hills (e.g., Baker et al, 2001;Carbotte et al, 2000;Carlut et al, 2004;Le Saout et al, 2014;Scheirer & Macdonald, 1995;Weiland & Macdonald, 1996). This morphology has been attributed to the influence of a hot spot (e.g., Carbotte et al, 2000;Carlut et al, 2004;Scheirer & Macdonald, 1995;Weiland & Macdonald, 1996), named "Mathematician hot spot" (Le Mougel et al, 2014Mougel et al, , 2015. A relationship between these features is supported by (1) the presence of the Mudskipper volcanic seamount ridge, located less than 5 km away from the ridge axis, on the western flank of the 16°N axial rise (e.g., Baker et al, 2001;Carlut et al, 2004;Macdonald et al, 1992;Weiland & Macdonald, 1996); (2) the location of the shallowest part of the dome, at 2,200 m depth, near the projected intersection of the Mudskipper volcanic chain with the ridge axis (15°42 0 N); (3) a geochemical anomaly identified in the axis-lavas that indicates a mixing between a MORB and a more enriched and heterogeneous source associated with the hot spot magmatism (Mougel et al, 2014(Mougel et al, , 2015; and (4) the presence of extinct spreading axes east of the ridge axis, indicating at least two westward jumps of 7 and 9 km in the direction of the hot spot at 150 and 300 kyr (e.g., Carbotte et al, 2000;Shah & Buck, 2006;Weiland & Macdonald, 1996).…”
Section: Morphological Segmentationmentioning
confidence: 99%
“…It is the broadest and shallowest segment of the entire northern EPR with an unusually prominent along-axial-ridge, up to 15 km wide at its base and up 750 m high with respect to the adjacent abyssal hills (e.g., Baker et al, 2001;Carbotte et al, 2000;Carlut et al, 2004;Le Saout et al, 2014;Scheirer & Macdonald, 1995;Weiland & Macdonald, 1996). This morphology has been attributed to the influence of a hot spot (e.g., Carbotte et al, 2000;Carlut et al, 2004;Scheirer & Macdonald, 1995;Weiland & Macdonald, 1996), named "Mathematician hot spot" (Le Mougel et al, 2014Mougel et al, , 2015. A relationship between these features is supported by (1) the presence of the Mudskipper volcanic seamount ridge, located less than 5 km away from the ridge axis, on the western flank of the 16°N axial rise (e.g., Baker et al, 2001;Carlut et al, 2004;Macdonald et al, 1992;Weiland & Macdonald, 1996); (2) the location of the shallowest part of the dome, at 2,200 m depth, near the projected intersection of the Mudskipper volcanic chain with the ridge axis (15°42 0 N); (3) a geochemical anomaly identified in the axis-lavas that indicates a mixing between a MORB and a more enriched and heterogeneous source associated with the hot spot magmatism (Mougel et al, 2014(Mougel et al, , 2015; and (4) the presence of extinct spreading axes east of the ridge axis, indicating at least two westward jumps of 7 and 9 km in the direction of the hot spot at 150 and 300 kyr (e.g., Carbotte et al, 2000;Shah & Buck, 2006;Weiland & Macdonald, 1996).…”
Section: Morphological Segmentationmentioning
confidence: 99%
“…In line with the work of Donnelly (2002), and Mougel et al. (2014, 2015), Mallick et al. (2019) confirmed that at least three components are necessary to account for the chemical and isotopic variability of the northern EPR: a depleted mantle, an enriched mantle, and an ancient gabbroic source (converted into pyroxenites).…”
Section: Geological Contextmentioning
confidence: 59%
“…To the west, the volcanic structures are attributed to the presence of a small heterogeneous hotspot (i.e., “Mathematician Hotspot”) responsible for the formation of the “Western plateau,” the “Northern Seamounts” and the “Mudskipper Seamounts” (Donnelly, 2002; Langmuir et al., 1998), while the origin of the “Eastern Seamounts” still remains uncertain. Finally, the tectonic and magmatic complexity of this region is also recorded in the geochemical composition of basalts from the 16°N segment, which displays a unique and remarkable isotopic variability (Donnelly, 2002; Mallick et al., 2019; Mougel et al., 2014, 2015).…”
Section: Geological Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…The high abundance of plagioclase is consistent with the low Ce/Pb and U/Pb the latter resulting in low 206 Pb/ 204 Pb isotopic compositions. As noticed by Donnelly (2002) and Mougel et al (2014Mougel et al ( , 2015 this component is different than any of the named mantle endmembers; they argue for a metagabbroic pyroxenite.…”
Section: 1029/2019gc008287mentioning
confidence: 82%